Effect of Low Red‐to‐Far‐Red Light on Stem Elongation and Pith Cell Development in Dicots - Linge Li; Yorrit van deKaa; Lotte van derKrabben; Ronald Pierik; Kaisa Kajala (Plant Direct)
ABSTRACT In dense canopies, light becomes a limiting factor for plant growth. Many plants respond to neighbor cues by growing taller to improve light capture, a phenomenon known as the shade avoidance syndrome (SAS). The major neighbor detection is via enrichment of far‐red (FR) light that leads to a low red:far‐red light ratio (R:FR), suppressing phytochrome activity. In tomato, low R:FR induces elongation of the internodes, but study into the role of different cell types in this response has remained limited. We characterized changes in cellular anatomy of the tomato internode in response to low R:FR and its accompanying changes in gene expression. We observed changes to the pith traits, including increases in pith layer number, pith cell diameter, and longitudinal cell length. We profiled the transcriptome in the entire internodes and in the hand‐dissected pith in the central cylinder of the internode in response to low R:FR treatment and identified transcription factors (TFs) of interest that were upregulated in the central cylinder, mostly GATA, TCP, and bZIPs. We then characterized FR responses in eight dicotyledonous species. Significant pith elongation was observed in species that exhibited a strong internode elongation response. The FR‐responsive expression of homologs of target GATA, TCP, and bZIP TFs in the central cylinder was conserved within the Solanaceae family. Overall, we discovered central cylinder gene expression patterns in SAS that are distinct from those of the entire internode, suggesting that some responses are unique and likely specific to vascular cell types such as pith. These patterns were conserved with close relatives of tomato but not in other dicot families we sampled, indicating that different molecular mechanisms drive FR responses in different dicots.